Construction of SnS2/SnO2 heterostructures with enhanced potassium storage performance. (15th October 2020) - Suo, Guoquan; Li, Dan; Feng, Lei; Hou, Xiaojiang; Ye, Xiaohui; Zhang, Li; Yu, Qiyao; Yang, Yanling; Wang, Wei (Alex)
Abstract: Increasing attention has been focused on potassium ion batteries (KIBs) as promising energy-storage system (ESS) owing to the abundance and low-cost of potassium resources. Here, SnS2 /SnO2 heterostructures were successfully fixed onto stainless steel mesh (SnS2 /SnO2 /SSM) through a facile two-step hydrothermal method and used as anodes for KIBs. Due to the advantages of SnS2 /SnO2 heterostructures and good conductivity of SSM substrate, the SnS2 /SnO2 /SSM anodes display enhanced electrochemical performance. The SnS2 /SnO2 /SSM anodes deliver specific capacity of 394 mA h g −1 at 50 mA g −1 over 100 cycles, better than SnO2 /SSM. Even at 500 mA g -1 after 250 cycles, high capacity of 155 mA h g −1 can still be obtained.